2017
DOI: 10.1007/s00213-016-4522-4
|View full text |Cite
|
Sign up to set email alerts
|

Feeding-modulatory effects of mu-opioids in the medial prefrontal cortex: a review of recent findings and comparison to opioid actions in the nucleus accumbens

Abstract: Rationale Whereas reward-modulatory opioid actions have been intensively studied in subcortical sites such as the nucleus accumbens (Acb), the role of cortical opioid transmission has received comparatively little attention. Objectives To describe recent findings on the motivational actions of opioids in the prefrontal cortex (PFC), emphasizing studies of food motivation and ingestion. PFC-based opioid effects will be compared/contrasted to those elicited from the Acb, to glean possible common functional pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 142 publications
(164 reference statements)
2
20
0
Order By: Relevance
“…It is not clear whether we would have seen similar effects of stimulating other excitatory glutamatergic inputs into the AcbSh although recent studies support a role for multiple inputs, including the prefrontal cortex and the thalamus, in reward seeking and consumption (Britt et al, 2012; Do-Monte et al, 2017; Prado et al, 2016; Selleck and Baldo, 2017; Stuber et al, 2011). For example, Britt et al found that mice will respond for activation of prefrontal, BLA, or hippocampual accumbal inputs (Britt et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…It is not clear whether we would have seen similar effects of stimulating other excitatory glutamatergic inputs into the AcbSh although recent studies support a role for multiple inputs, including the prefrontal cortex and the thalamus, in reward seeking and consumption (Britt et al, 2012; Do-Monte et al, 2017; Prado et al, 2016; Selleck and Baldo, 2017; Stuber et al, 2011). For example, Britt et al found that mice will respond for activation of prefrontal, BLA, or hippocampual accumbal inputs (Britt et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
“…Second, although photoactivation interrupted alcohol drinking, animals continued to interact with the sipper tube during the alcohol drinking test. These within-test dissociations are intriguing and raise important questions about control over the sequence of reward-seeking actions, specifically between approach and “terminal”, consummatory, responses, which are proposed to engage different learning systems (Chang and Smith, 2016; Naeem and White, 2016; Selleck and Baldo, 2017). The findings suggest the interesting possibility that consummatory responses/terminal responses, may be more sensitive to the influence of BLA-AcbSh innervation than more distal actions within the behavioral chain, a possibility awaiting future testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Allen and DeYoung 2016) and its genetic variation has been also pointed to the opiate system, due to its involvement in the hedonic response to the stimulus (Peciña et al 2006). It is, therefore, possible that the endogenous opioid system via modulation of amygdala and medial prefrontal cortex (Tejeda et al 2015; Selleck and Baldo 2017), most used regions in the connections of Face , mediate both the perception of faces (Martin et al 2006) and the social bonding (Pasternak and Pan 2013). We thus suggest that functional connectivity within the Face network in Men is mostly related to the “Affiliative” aspect of Extraversion.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MOP receptors mediate the rewarding properties of other nonopioid drugs of abuse, such as cocaine, nicotine, and ethanol . Furthermore, MOP receptors are involved in natural reward, such as feeding . Feeding was shown to increase endogenous opioid release …”
Section: Functions Of Each Opioid Receptor Subtypementioning
confidence: 99%